The role of phosphorylcreatine and creatine in the regulation of mitochondrial respiration in human skeletal muscle - Walsh, B; Tonkonogi, M; Soderlund, K; Hultman, E; Saks, V; Sahlin, K (The Journal of physiology, 2001)
The role of phosphorylcreatine (PCr) and creatine (Cr) in the regulation of mitochondrial respiration was investigated in permeabilised fibre bundles prepared from human vastus lateralis muscle. Fibre respiration was measured in the absence of ADP ( VÌ 0 ) and after sequential additions of submaximal ADP (0.1 m m ADP, VÌ submax ), PCr (or Cr) and saturating [ADP] ( VÌ max ). VÌ submax increased by 55% after addition of saturating creatine ( P < 0.01; n = 8) and half the maximal effect was obtained at 5 m m [Cr]. In contrast, VÌ submax decreased by 54% after addition of saturating phosphorylcreatine ( P < 0.01; n = 8) and half the maximal effect was obtained at 1 m m [PCr]. VÌ max was not affected by Cr or PCr. VÌ submax was similar when PCr and Cr were added simultaneously at concentrations similar to those in muscle at rest (PCr/Cr = 2) and at low-intensity exercise (PCr/Cr = 0.5). At conditions mimicking high-intensity exercise (PCr/Cr = 0.1), VÌ submax increased to 60% of VÌ max ( P < 0.01 vs . rest and low-intensity exercise). Eight of the subjects participated in a 16 day Cr supplementation programme. Following Cr supplementation, VÌ 0 decreased by 17% ( P < 0.01 vs . prior to Cr supplementation), whereas ADP-stimulated respiration (with and without Cr or PCr) was unchanged. For the first time evidence is given that PCr is an important regulator of mitochondrial ADP-stimulated respiration. Phosphorylcreatine decreases the sensitivity of mitochondrial respiration to ADP whereas Cr has the opposite effect. During transition from rest to high-intensity exercise, decreases in the PCr/Cr ratio will effectively increase the sensitivity of mitochondrial respiration to ADP. The decrease in VÌ 0 after Cr supplementation indicates that intrinsic changes in membrane proton conductance occur.